Open reduction and internal fixation of the bilateral proximal humeral fracture dislocation with head splitting in an active young adult: a rare case - Okhovatpour , Mohammad Ali; Safaei, Yaser; Faramarzi, Behrooz; Sadighi, Mehrdad (Researcher Bulletin of Medical Sciences, 2021)
Proximal humeral fracture is a common injury particularly in elderly. A proper management of these fractures is very challenging, based on the various characteristics of patient, fracture anatomy, equipment and the surgeon experience. Bilateral PHF is a rare condition, which almost always caused by seizure, electric shock and trauma, respectively. An appropriate treatment of these patients needs especial attention to obtain a good clinical outcome. We report a 29-year-old patient who suffered from bilateral proximal humeral fracture with posterior dislocation and splitted humeral head due to the combined mechanism of injury including severe trauma after high voltage electric shock. We did not find similar case(s) reported before in the literature. The patient treated with bilateral open reduction and internal fixation (ORIF). He was able to do his daily activities after 6 months